Carnosinase concentration, activity, and CNDP1 genotype in patients with type 2 diabetes with and without nephropathy - Zhang, Shiqi; Albrecht, Thomas; Peters, Verena; Schmitt, Claus P.; Lammert, Alexander; Krämer, Bernhard; Yard, Benito A.; Hauske, Sibylle J. (Amino acids, 2019)
This study assessed if serum carnosinase (CNDP1) activity and concentration in patients with type 2 diabetes mellitus (T2D) with diabetic nephropathy (DN) differs from those without nephropathy. In a cross-sectional design 127 patients with T2D with DN ((CTG)5 homozygous patients n = 45) and 145 patients with T2D without nephropathy ((CTG)5 homozygous patients n = 47) were recruited. Univariate and multivariate regression analyses were performed to predict factors relevant for serum CNDP1 concentration. CNDP1 (CTG)5 homozygous patients with T2D with DN had significantly lower CNDP1 concentrations (30.4 ± 18.3 vs 51.2 ± 17.6 µg/ml, p < 0.05) and activity (1.25 ± 0.5 vs 2.53 ± 1.1 µmol/ml/h, p < 0.05) than those without nephropathy. This applied for patients with DN on the whole, irrespective of (CTG)5 homozygosity. In the multivariate regression analyses, lower serum CNDP1 concentrations correlated with impaired renal function and to a lesser extend with the CNDP1 genotype (95% CI of regression coefficients: eGFR: 0.10-1.94 (p = 0.001); genotype: − 0.05 to 5.79 (p = 0.055)). Our study demonstrates that serum CNDP1 concentrations associate with CNDP1 genotype and renal function in patients with T2D. Our data warrant further studies using large cohorts to confirm these findings and to delineate the correlation between low serum CNDP1 concentrations and renal function deterioration in patients with T2D.